AKTIVITAS DAYA HAMBAT EKSTRAK ETANOL DAUN BELIMBING WULUH DAN SODIUM HIPOKLORIT TERHADAP Enterococcus faecalis (In Vitro) - Rohmatun Nisa; Isyana Erlita; Lia Yulia Budiarti (FKG Unlam, 2017)
Background: Enterococcus faecalis is gram-positive bacteria that cause the failure of root canal treatment. Effective method to eliminate Enterococcus faecalis in root canal by using sodium hypochlorite (NaOCl) 5.25%. Natural materials can be inhibiting the growth of gram-positive bacteria including Enterococcus sp. is a compound of tannins, saponins and flavonoids. Purpose: This study aims to know the differences of inhibition of the activity in ethanol extract of wuluh starfruit leaves (Averrhoa bilimbi L.) and sodium hypochlorite (NaOCl) 5.25% against Enterococcus faecalis. Methods: This study was using true experimental research design, post test-only with control group design that the treatments which being tested were ethanol extract of starfruit leaf 40%, 50%, 60% and NaOCl 5.25%. Antibacterial effect tested with diffusion method and the parameters measured by the amount of inhibition zone formed in the media of the test. The data analysis using Kruskall-Wallis test and next testing of Mann Whitney. Results: The results showed that ethanol extract of wuluh starfruit leaf with concentration 40%, 50%, 60% and NaOCl 5.25% against Enterococcus faecalis as measured from inhibition zone are 13.37 mm, 16.50 mm, 18 39 mm and 21.30 mm. The data analysis using Kruskall-Wallis test, the results this research is p=0.000 (p<0.05) then there are a differences in the inhibitory activity between each group, and next testing of Mann Whitney that results is p=0.002 (p<0.05) show meaningful differences between each group. Conclusion: The conclusion is the differences in the inhibitory activity of ethanol extract of starfruit leaf extract and sodium hypoclorite 5,25% against Enterococcus faecalis.